Experimental study of the mechanical behavior of an explanted mesh: The influence of healing. (January 2017) - Morch, A.; Pouseele, B.; Doucède, G.; Witz, J.-F.; Lesaffre, F.; Lecomte-Grosbras, P.; Brieu, M.; Cosson, M.; Rubod, C.
Abstract: To better understand the in vivo mechanical behavior of synthetic mesh implants, we designed a specific experimental protocol for the mechanical characterization of explanted mesh under uniaxial tension. The implantation of a mesh leads to the development of scar tissue and the formation of a new composite made of native tissue, a mesh implant and scar tissues. This study focused on three points: determining the minimum representative size of mesh implants required for mechanical test samples, highlighting the influence of healing, and defining the healing time required to ensure stabilized mechanical properties. First, we determined the minimum representative size of mesh implants for the mechanical characterization with a study on a synthetic composite made of mesh and an elastomeric matrix mimicking the biological tissues. The size of the samples tested was gradually decreased. The downsizing process was stopped, when the mechanical properties of the composite were not preserved under uniaxial tension. It led to a sample representative size 3 cm long and 2 cm wide between the grips. Then an animal study was conducted on Wistar rats divided into eight groups. One group was set as control, consisting of the healthy abdominal wall. The other seven groups underwent surgery as follows: one placebo (i.e., without mesh placement), and six with a mesh installation on the abdominal wall and healing time. The rats were sacrificed after different healing times ranging from 1 to 5 months. We observed the influence of healing and healing time on the mechanical response under uniaxial tension of the new composite formed by scar, native tissue, and textile. It seems that 2 months are required to ensure the stabilization of the mechanical properties of the implanted mesh. We were not able to tell the control group (native abdominal wall) from the placebo group (native and scar tissue). This protocol was tested on two different prostheses after 3 months of healing. With this protocol, we were able to differentiate one mesh from another after host integration. Abstract : Highlights: After implantation, synthetic mesh takes part in a biological composite. A mechanical testing protocol is developed to characterize such composites. Mesh composite mechanical answer is dependant on sample size. Healing time is a key-parameter for the evaluation of mechanical properties. Two months of healing are required to observe a stabilized mechanical answer.